CONSIDERACIONES EN TORNO A LA DEFINICIÓN DEL CONCEPTO DE COMPETENCIA COMUNICATIVA PROFESIONAL PEDAGÓGICA: CONSIDERATIONS ABOUT THE DEFINITION OF THE CONCEPT PROFESSIONAL PEDAGOGIC COMMUNICATIVE COMPETENCE - Más Sánchez, Pablo Raúl (Opuntia Brava, 2018)
En el artículo se efectúa un análisis de la evolución de las comprensiones al definir el concepto competencia comunicativa profesional pedagógica que han ganado espacio consensual en las opiniones de la comunidad científica y académica, como base para fundamentar una nueva definición que supere el reduccionismo imperante en su tratamiento y permita delinear su modelación pedagógica, así como las vías para su formación en la preparación inicial del personal docente en las condiciones de la universalización de la enseñanza. Se esclarece la relación entre habilidades, estilos y competencia comunicativa, a partir de la revelación de los vínculos existentes entre ellas. ABSTRACT The article includes some considerations about the definition of the concept Communicative Competence on the light of the approach by Competencies, which is very important for the contemporary scientific community. The authors give some approximations in a very reflexive way, about the study of some of the aspects that in our consideration have conditioned the different interpretations that have been made about this problematic aspect through its history, that is, the cases of the linguistic vision and/or psychological. We put into the specialists and researchers consideration, as well as, those who have carried studies on communication, our view points on the matter and a new way for understanding this phenomenon, offering also the definition of new concept "Pedagogical and professional Communicative Competence. KEY WORDS: Professional pedagogic communicative competence; communication; relation among skills, styles and communicative competence.